Методологические принципы в постнеклассической физике - Владленова, Илиана Викторовна (УАН ТОВ "НВП "ВІР", 2010)
Рассмотрены методологические принципы постнеклассической физики. Эти принципы артикулируют человеческие смыслы, потенциально содержат в себе новые исследовательские программы для других наук. Их всеобщий статус определяется широким познавательным и социокультурным контекстом.

Methodological principles of postneklassical physics are considered in the article. These principles are articulated by human senses, contain the new research programs for other sciences. Their universal status is determined a wide cognitive and sociokultural context.
Methodological principles of postneklassical physics
Keywords: методологический принцип; постнеклассическая физика; смысл; смысл; methodological principle; postneklassical physics; sense; methodology